Journal of the Constitutional Convention of Connecticut, Aug. 26 - Sept. 16, 1818 : (Book the 1st. and Book the 2nd.) (Connecticut State Library, 1938)
Manuscript journals of the 1818 Connecticut State Constitutional Convention compiled and titled by the Connecticut State Library in 1938. Includes some annotated excerpts from printed documents.